Can prosthesis type influence the recurrence of infective endocarditis after surgery for native valve endocarditis? A propensity weighted comparison. (19th May 2021) - Rubino, Antonino S; Della Ratta, Ester E; Galbiati, Denise; Ashurov, Rasul; Galgano, Viviana L; Montella, Antonio P; De Feo, Marisa; Della Corte, Alessandro
Abstract:  : OBJECTIVES: Our goal was to investigate whether the incidence of valve-related adverse events might be different depending on the valve substitute after valve replacement for left-sided native valve endocarditis. METHODS: We assessed the long-term freedom from recurrence, reoperation and survival of 395 patients who had valve replacements for native valve endocarditis (314 mechanical vs 81 biological). Age <18 years, reoperation, prosthetic endocarditis, right valve involvement, valve repair and homograft implants were the main exclusion criteria. The balance between the 2 groups was addressed by weighting the results on the inverse of the propensity score. RESULTS: After inverse probability of treatment weighting (IPTW), freedom from recurrence of infective endocarditis was not significantly different (mechanical 84.1 ± 3.2% vs 50.6 ± 21.7%; P  = 0.29) nor was freedom from reoperation different (mechanical 85.7 ± 3.1% vs biological 50.9 ± 21.9%; P  = 0.29). Excluding competing deaths, patients receiving a bioprosthesis had a similar subdistribution hazard of the above end points compared to recipients of a mechanical valve [recurrence IPTW: hazard ratio (HR) 1.631, 95% confidence interval (CI) 0.756–3.516; P  = 0.21; reoperation IPTW-HR 1.737, 95% CI 0.780–3.870; P  = 0.18]. Mechanical valves were associated with improved long-term survival (34.9 ± 5.8% vs 10.5 ± 7.4% at 30 years; P  = 0.0009; in particular: aortic valve subgroup 41.6 ± 9.3% vs 10.1 ± 8.2%; P  < 0.0001), although the hazard of cardiovascular mortality did not favour either valve type (IPTW: HR 1.361, 95% CI 0.771–2.404; P  = 0.29). CONCLUSIONS: Our analysis showed a clinical trend in favour of mechanical valves as valve substitutes for native valve endocarditis, especially in the aortic position. In view of long-term freedom from adverse events, the choice of the valve type should be tailored according to patient characteristics and specific clinical conditions. Abstract : Infective endocarditis is a challenging clinical condition, secondary to an infection of the valvular endothelium and the paravalvular apparatus, which deserves cardiac surgery to eradicate the infection and to re-establish adequate valve competence [1, 2].